Physical-medical integration policies and health equity promotion in China: a text analysis based on policy instruments - Mingyuan Zhao; Lishu Yang; Baoshan Qian; Yun Yang; Gongbo Wei; Chen Li (International Journal for Equity in Health)
Abstract Background In China, although policies promoting physical-medical integration have received widespread national attention, the existence and manifestation of health equity promotion within these policies still require further exploration. Methods This study used text analysis to examine 62 policy documents on physical-medical integration issued by various Chinese governmental departments from June 2016 to June 2023, utilizing KH Coder software for qualitative analysis. Results The analysis revealed a strong emphasis on public health, promoting health management and disease prevention across all age groups. The policies aimed to ensure the equitable distribution of health care resources, particularly those benefiting rural and underserved populations, and they underscored the importance of collaboration among the government, sports, and health care sectors to foster sports-health integration. Conclusion The integration of sports and health policy is a key initiative to address chronic diseases in China, as it aligns closely with health equity principles. Achieving these goals requires ongoing improvements in implementation and monitoring, with a focus on the diverse needs of various populations.